Increasing Use of Research Findings in Improving Evidence-Based Health Policy at the National Level - Budiharsana, Meiwita (UI Scholars Hub, 2017)
In February 2016, the Minister of Health decided to increase the use of research findings in improving the quality of the national health policy and planning. The Ministry of Health has instructed the National Institute of Health Research and Development or NIHRD to play a stronger role of monitoring and evaluating all health programs, because “their opinion and research findings should be the basis for changes in national health policies and planning”. Compared to the past, the Ministry of Health has increased the research budget for evidence-based research tremendously. However, there is a gap between the information needs of program and policy-makers and the information offered by researchers. A close dialogue is needed between the users (program managers, policy makers and planners) and the suppliers (researchers and evaluators) to ensure that the evidence-based supplied by research is useful for programs, planning and health policy.